Tislelizumab-induced type 1 diabetic ketoacidosis in a patient with small cell lung cancer: a case report - Zhu, Jie; Wang, Wen-jie (Frontiers in Oncology, 2025)
This report presented a case of 71-year-old man diagnosed with extensive-stage small cell lung cancer (ES-SCLC) who developed type 1 diabetic ketoacidosis (DKA) after 3 cycles of tislelizumab plus chemotherapy for the first time. The patient had no history of diabetes mellitus (DM). According to medical history and laboratory examination, the case was definitely diagnosed new-onset type 1 diabetic ketoacidosis induced by tislelizumab, a kind of immune checkpoint inhibitor. Despite the incidence of immune checkpoint inhibitor-induced type 1 diabetes mellitus (ICI-T1DM) is rare, the development of ICI-T1DM, especially type 1 diabetic ketoacidosis is life-threating without blood glucose monitoring and insulin therapy. Early identification of hyperglycemia and C-peptide depletion, as well as routine blood glucose monitoring during ICI treatment is essential to avoid lethal endocrine immune-related adverse event (irAE).